Evaluation of long-term survival in patients with severe comorbidities after endoscopic submucosal dissection for esophageal squamous cell carcinoma - Hirano, Shinji; Nagami, Yasuaki; Yamamura, Masafumi; Tanoue, Kojiro; Sakai, Taishi; Maruyama, Hirotsugu; Ominami, Masaki; Nadatani, Yuji; Fukunaga, Shusei; Otani, Koji; Hosomi, Shuhei; Tanaka, Fumio; et al. (Surgical endoscopy, 2022)
Background Endoscopic submucosal dissection (ESD) is becoming widely popular as a less invasive treatment option for superficial esophageal squamous cell carcinoma. However, data on long-term survival after esophageal ESD in patients with severe comorbidities are limited. This study aimed to evaluate long-term survival after ESD in such patients. Methods Altogether, 584 consecutive patients underwent esophageal ESD at our institution from May 2004 to September 2016. Based on the American Society of Anesthesiologists Physical Status (ASA-PS) classification system, patients were grouped according to severe (ASA-PS ≥ 3) or non-severe comorbidities (ASA-PS 1/2). The overall survival (OS), disease-specific survival (DSS), and risk factors for mortality were compared between the groups using a propensity score matching analysis. Results In a matched cohort of 69 pairs, the 5-year OS rate was poorer in ASA-PS 3 patients than in ASA-PS 1/2 patients (63.9% vs. 92.5%, P < 0.01), while the 5-year DSS rate was similar between the groups (100% vs. 100%). The mortality rate was significantly higher in ASA-PS 3 patients than in ASA-PS 1/2 patients (hazard ratio 3.47; 95% confidence interval 1.79–6.74; P < 0.01). Death due to exacerbation of comorbidities was significantly more frequent in ASA-PS 3 patients than in ASA-PS 1/2 patients (42.4% vs. 8.3%, P < 0.04). Conclusion Because of the exacerbation of comorbidities, patients with severe comorbidities had poorer long-term outcomes after esophageal ESD than those with non-severe comorbidities. Further studies will be necessary to evaluate esophageal ESD in patients with severe comorbidities.